Pengaruh Profitabilitas dan Likuiditas terhadap Opini Audit Going Concern - Zalikha, Zalikha; Ariska, Emalia; Mulyadi, Mulyadi; Yusuf, M (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This research aims to find out how Profitability and Liquidity influence Going Concern Audit Opinions in manufacturing companies listed on the Indonesia Stock Exchange for the 2021–2023 period. The population in this study are manufacturing companies in the Consumer Goods Industry sector listed on the Indonesian Stock Exchange for the 2021–2023 period. Sampling was carried out using the Purposive Sampling method. The type of data used is secondary data. The results of this research show that the Profitability variable has a significant negative effect on the Going Concern Audit Opinion, while the Liquidity variable does not have a significant effect on the Going Concern Audit Opinion. However, the variables Profitability and Liquidity simultaneously have a significant effect on the Going Concern Audit Opinion.